Perubahan Komponen Kimia Fungsional pada Umbi, Tepung, dan Beras Analog Ubi Jalar Ungu - Haikal Samhana; Dias Indrasti (Department of Food Science and Technology (ITP), Faculty of Agricultural Technology, Bogor Agricultural University (IPB) in collaboration with the Indonesian Food and Beverage Association (GAPMMI), the National Agency of Drug and Food Control, and th, 2024)
The purple sweet potato tuber, rich in functional chemical components, offers potential for development into high-value products such as flour, which can then be processed into analog rice. This research aims to evaluate the changes in functional chemical components–namely moisture, ash, protein, fat, carbohydrates, anthocyanin, and β-carotene–along with antioxidant activity during the processing of purple sweet potato tubers into flour and analog rice. The chemical composition of the tubers was found to be as follows: moisture content of 78.00% on a wet basis (wb), ash content of 9.70% on a dry basis (db), fat content of 5.47% (db), protein content of 26.93% (db), carbohydrate content of 58.41% (db), anthocyanin content of 31.79 mg/100 g (db), β-carotene content of 17.73 mg/100 g (db), and antioxidant activity of 65.70%. The composition of the resulting flour included water (6.71% wb), ash (2.40% db), fat (1.06% db), protein (3.80% db), carbohydrate (92.75% db), anthocyanin (3.47 mg/100 g db), β-carotene (1.51 mg/100 g db), and antioxidant activity (45.59%). The chemical content of the analog rice was as follows: water (8.43% wb), ash (1.78% db), fat (1.62% db), protein (4.13% db), carbohydrate (92.50% db), anthocyanin (0.71 mg/100 g db), β-carotene (1.05 mg/100 g db), and antioxidant activity (8.38%). Processing the tubers into flour resulted in a reduction of fat, protein, anthocyanins, β-carotene, and antioxidant activity, while carbohydrate content increased. Similarly, the conversion of flour into analog rice led to decreased levels of carbohydrates, anthocyanins, β-carotene, and antioxidant activity, whereas fat and protein levels increased after transfor-mation into analog rice. The processing stages that significantly contributed to these changes in chemical components included drying, formulation, and extrusion.